2022
DOI: 10.1186/s13256-022-03462-z
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis and tachycardia–bradycardia syndrome: a case report

Abstract: Background Systemic sclerosis is a multisystemic character autoimmune disease. It is characterized by vascular dysfunction and progressive fibrosis affecting mainly the skin but also different internal organs. All heart structures are commonly affected, including the pericardium, myocardium, and conduction system. However, tachycardia–bradycardia syndrome is not common in the literature as a cardiac complication of systemic sclerosis. Case presentation We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…3 Despite being a less common variant, ssSSc often presents challenges in diagnosis due to its varied clinical manifestations and potential underdiagnosis. 4,5 Delays in the diagnosis of ssSSc can have detrimental consequences, as the disease frequently involves vital internal organs such as the cardiovascular and respiratory systems. Studies have indicated variable 10-year survival rates ranging from 50% to 84% in SSc, highlighting the importance of early identification and intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Despite being a less common variant, ssSSc often presents challenges in diagnosis due to its varied clinical manifestations and potential underdiagnosis. 4,5 Delays in the diagnosis of ssSSc can have detrimental consequences, as the disease frequently involves vital internal organs such as the cardiovascular and respiratory systems. Studies have indicated variable 10-year survival rates ranging from 50% to 84% in SSc, highlighting the importance of early identification and intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology of ssSSc remains poorly understood, with estimates suggesting that it accounts for approximately 5% of all SSc cases 3 . Despite being a less common variant, ssSSc often presents challenges in diagnosis due to its varied clinical manifestations and potential underdiagnosis 4,5 …”
Section: Introductionmentioning
confidence: 99%